Estudo do sistema de lajes mistas com forma de aço incorporada empregando concreto estrutural leve - Luciano Carvalhais Gomes (2001)
The results of an experimental investigation on the behavior and strength of one-way single span composite slabs with ribbed decking and lightweight concrete are presented. The lightweight structural concrete was produced employing conventional techniques and substituting the coarse aggregate by expanded clay. Prototypes with different dimensions were built with steel deck MF 75 manufactured by METFORM S. A . The specimens were tested, after the concrete curing, in a simply supported condition with two line loads equidistant of each support. The test results indicate a similar behavior in comparison to composite slabs with normal weight concrete. Similar results were alsoobtained with respect to failure mode and ultimate load capacity, including the estimation of design loads through the semi-empirical m and k method.